2017
DOI: 10.1111/vec.12593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of small and large‐bore thoracostomy tubes for pleural space evacuation in canine cadavers

Abstract: SB and LB thoracostomy tubes demonstrated similar efficacy in removing known amounts of air, LV fluid, and HV fluid from the pleural space of canine cadavers. Further study is necessary to determine if SB and LB thoracostomy tubes demonstrate similar efficacy in clinical veterinary patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In this regard, the management of pyothorax represents a challenge due to the thickness of the exudate, especially in the chronic stages, with subsequent failure of the drain. Nonetheless, SBTTs have recently been suggested to be an effective alternative to LBTTs for the management of pleural space disease, including pyothorax, in both humans and animals (Valtolina and Adamantos, 2009;Hooper et al, 2015b;Filosso et al, 2016;Fetzer et al, 2017;Hallifax et al, 2017). http://www.openveterinaryjournal.com S. Del Magno et al Open Veterinary Journal, (2020, Vol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the management of pyothorax represents a challenge due to the thickness of the exudate, especially in the chronic stages, with subsequent failure of the drain. Nonetheless, SBTTs have recently been suggested to be an effective alternative to LBTTs for the management of pleural space disease, including pyothorax, in both humans and animals (Valtolina and Adamantos, 2009;Hooper et al, 2015b;Filosso et al, 2016;Fetzer et al, 2017;Hallifax et al, 2017). http://www.openveterinaryjournal.com S. Del Magno et al Open Veterinary Journal, (2020, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracocentesis is usually followed by thoracic tube placement associated with systemic antimicrobial administration (Tillison, 1997;MacPhail, 2007;Sigrist, 2015;Sherman et al, 2020). Thoracostomy drains are divided into large-bore thoracostomy tubes (LBTTs) (14-16 Fr for cats and 24-26 Fr for dogs) (Drobatz et al, 2018) and small-bore thoracostomy tubes (SBTTs) (10-14 Ga) (Valtolina and Adamantos, 2009;Fetzer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tubes are placed with a Seldinger or modified Seldinger technique and do not require general anaesthesia to place 28. A cadaveric study showed that there was no difference in recovery of known amounts of air, low‐viscosity fluid and high‐viscosity fluid from small‐bore versus large‐bore thoracostomy tubes 30. Financial limitations directed the course of care for the patient in this report.…”
Section: Discussionmentioning
confidence: 89%
“…28 A cadaveric study showed that there was no difference in recovery of known amounts of air, low-viscosity fluid and high-viscosity fluid from small-bore versus large-bore thoracostomy tubes. 30 Financial limitations directed the course of care for the patient in this report. The ability to place a guidewire-inserted chest tube without general anaesthesia facilitated evacuation of the haemothorax, collection of blood in aseptic fashion, and allowed autologous blood transfusion to be given at a substantially reduced cost compared with placement of large-bore thoracostomy tube under general anaesthesia or administration of an allogenic blood transfusion.…”
Section: Learning Pointsmentioning
confidence: 95%